KEBERTAHANAN PENGULAT DI DESA PEDAWA, KECAMATAN BANJAR, KABUPATEN BULELENG - Pangestu, Dhi'fa Hafizha; Wiasti, Ni Made; Aliffiati, Aliffiati (FISIP Universitas Malikussaleh, 2024)
Pengulat is a local term used in Pedawa Village to refer to a craftsman of woven bamboo. The number of pengulat in Pedawa Village consist of 21 peoples. Pengulat in Pedawa Village dominated by the older people, so there is a threat of ending the pengulat generation if the younger generation in Pedawa Village does not continue and develop this economic potentials. This research aims to describe and explain the resistance of pengulat in Pedawa Village, Banjar District, Buleleng Regency. This research is qualitative by using ethnographic method (observation and interview) and also literature study. The theory that used in this research is the structural functional theory by A.R. Radcliffe Brown and the theory of motivation by David McClelland. Based on the data obtained in this research, the potentials and problem experienced by pengulat during doing their work comes from two factors, potentials and probles that comes from the natural resources and potentials and problems that comes from the hunan resources.